MOLECULAR SIEVE AS AN ECONOMICAL ROUTE FOR THE REMOVAL OF HYDROGEN SULFIDE (H2S) AND TETRAHYDROTHIOPHENE(THT) FROM NATURAL GAS FOR FUEL CELL APPLICATIONS - Akhtar, M. N.; Qureshi, A. H.; Guard, B. (The Nucleus, 2020)
The removal of hydrogen sulfide (H2S) and tetrahydrothiophene (THT) from the natural gas has been studied by employing two kinds of sorbents, i. e., compounds of sulfur-absorbing and sulfur-adsorbing materials. For the removal of sulfur compounds, a system was designed, established and operated for 2000 hours. Determination of the life-cycle assessment and feasibility of materialâ€™s effectiveness were also carried out. The same experiment was repeated by using a substitute (molecular sieve) and the treated gas coming out of the cleaning system was examined every 4-hour-run time by DrÃ¤ger gas detector pump (DGDP) for the presence of H2S and THT. The results were very encouraging for this material. The molecular sieve is found highly economical as a single material with a simple design when compared with the set of sorbents tried earlier. The sulfur-free natural gas is required as feedstock for the production of hydrogen gas which will be consumed by the proton exchange membrane fuel cells for smooth functioning, keeping in view the high efficiency of the system.